Uresničevanje posebnih pravic pripadnikov italijanske narodne skupnosti - Burra, Aleksandro (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2022)
The role of bilingual institutions is crucial in developing bilingualism. The study proposes a performance management system to find out how one of the key cultural institutions in the ethnically mixed area – the Central Library Srečko Vilhar Koper – implements the special rights of members of the Italian national community in terms of the library’s operations and activities. The research method applied was case study. The descriptive method was used in the analysis of the research problem and research data. The analysis involved a set of five factors, and the success achieved by each factor was scored. The results suggest that the library properly implements institutional bilingualism. Nevertheless, there is still room for improvement to achieve a full implementation of bilingualism.
Keywords: institucionalna dvojezičnost; italijanska manjšina; manjšinska zakonodaja; Slovenija; splošne knjižnice; uresničevanje zakonsko določenih posebnih pravic